If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (1 + -1w)(4w + 6) = 0 Reorder the terms: (1 + -1w)(6 + 4w) = 0 Multiply (1 + -1w) * (6 + 4w) (1(6 + 4w) + -1w * (6 + 4w)) = 0 ((6 * 1 + 4w * 1) + -1w * (6 + 4w)) = 0 ((6 + 4w) + -1w * (6 + 4w)) = 0 (6 + 4w + (6 * -1w + 4w * -1w)) = 0 (6 + 4w + (-6w + -4w2)) = 0 Combine like terms: 4w + -6w = -2w (6 + -2w + -4w2) = 0 Solving 6 + -2w + -4w2 = 0 Solving for variable 'w'. Factor out the Greatest Common Factor (GCF), '2'. 2(3 + -1w + -2w2) = 0 Factor a trinomial. 2((1 + -1w)(3 + 2w)) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(1 + -1w)' equal to zero and attempt to solve: Simplifying 1 + -1w = 0 Solving 1 + -1w = 0 Move all terms containing w to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1w = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1w = 0 + -1 -1w = 0 + -1 Combine like terms: 0 + -1 = -1 -1w = -1 Divide each side by '-1'. w = 1 Simplifying w = 1Subproblem 2
Set the factor '(3 + 2w)' equal to zero and attempt to solve: Simplifying 3 + 2w = 0 Solving 3 + 2w = 0 Move all terms containing w to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 2w = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 2w = 0 + -3 2w = 0 + -3 Combine like terms: 0 + -3 = -3 2w = -3 Divide each side by '2'. w = -1.5 Simplifying w = -1.5Solution
w = {1, -1.5}
| a=b/c | | 8-4t=6t-22 | | 7x+4=24 | | 15s-8c=5c+48 | | 15X-19+4X+53-8X=2X-43+86+9X+35+-X | | 3m+24=7m | | -1/2m+8=10 | | 68=-2(m+5)+m | | (3x-8)(x+1)=0 | | 3z+24=-7z | | 5=5(x-4)+5-4x | | 4q+2=4 | | 68=-2 | | 1/7(x+2)=4 | | 0.4(0.71+6x)=3.2x | | a/15=b | | let(f)=5x^2-8x+3 | | 8X+59-5X=X-84+242+X | | 8+6+2x=8x | | 4t-2=1 | | x+2=4(4x-3) | | 2x=4-6 | | 3/4(x-16)=-51/4 | | 8p+8=3p-2 | | 6(c-9)=-30 | | 1x+3x+4=4x | | 5X-74+8X=7X+148+5X | | -13-9y=13 | | 4x^2-8x+6=0 | | 3n-11=4 | | 8q^2-10+3=0 | | 7+1=m |